2006
DOI: 10.1111/j.1468-5906.2006.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Inward, Outward, Upward Prayer: Scale Reliability and Validation

Abstract: This study provides support for a model that conceptualizes prayers as the means to establish cognitive connections in three directions: inward (self-connection); outward (human-human connection); and upward (human-divine connections). A confirmatory factor analysis demonstrates a single general prayer factor divisible into three subfactors that are in turn comprised of eight discrete scales. Measures of general religiosity, the need for structure, religious styles of coping, well-being, life-satisfaction, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 23 publications
7
89
2
1
Order By: Relevance
“…The subscales loaded onto second order intentionality factors with loadings all over .65. Later, CFA replicated these findings (Ladd & Spilka, 2006). Each of the eight scales again demonstrated adequate reliability with all alpha coefficients over .70.…”
Section: Next Is Factor 2 With An Emphasis On Upward Connection To Gsupporting
confidence: 61%
See 1 more Smart Citation
“…The subscales loaded onto second order intentionality factors with loadings all over .65. Later, CFA replicated these findings (Ladd & Spilka, 2006). Each of the eight scales again demonstrated adequate reliability with all alpha coefficients over .70.…”
Section: Next Is Factor 2 With An Emphasis On Upward Connection To Gsupporting
confidence: 61%
“…They found that there were indeed three distinct second-order factors of prayer (see Figure 1), but they reflected intentions of prayer, rather than direction of connection. Though initial model development supported a single overall prayer factor, it has not consistently been replicated (Ladd & Spilka, 2006, Breslin & Lewis, 2010. The first factor is named Collectivistic Prayer because the three prayer types loading onto this factor reflect characteristics of a collectivist culture.…”
Section: Upon Scale Construction Ladd and Spilka (2002) Tested For Smentioning
confidence: 99%
“…The extent to which a perceived attempted prayer is equivalent to an actual prayer is a theologically complex issue beyond the scope of this paper. With regard to prayer, Ladd and Spilka (2006) noted that there was often a significant divergence between official theological positions and "lived" theology. For our purpose, we focus on the self-reported nature of the individual's experience.…”
Section: Prayer Fmri and Contextmentioning
confidence: 99%
“…Those individualized prayers are, in turn, divergent in their content and the extent to which that content is more affective, cognitive, or behaviorally oriented may well shift cortical activation patterns. Analyses that do not take into consideration these and other nuances associated with the multidimensional nature of prayer run the risk of suppressing interesting information by averaging across participants (Ladd & Spilka, 2006).…”
Section: Critical Issuesmentioning
confidence: 99%
“…On this account, factor one comprised two outward and one inward scale (intercession, examination, and suffering); factor two comprised one inward and two upward scales (tears, rest, and sacrament); and factor three comprised two outward scales (radical and petition). This tradition of research has been developed further by Spilka (2006), andLadd, Ladd, Harner, Swanson, Metz, St Pierre andTrnka (2007).…”
mentioning
confidence: 99%